Managing and using information systems : a strategic approach - Pearlson, Keri E.; Saunders, Carol S. (Hoboken, NJ : John Wiley & Sons, 2013)
From the cover. Information systems are at the heart of virtually every business process, and decision. Like previous editions, this fifth edition of Managing and Using Information Systems by Pearlson and Saunders gives you the foundation to become a knowledgeable participant in information systems decisions and to manage information for competitive advantage. This edition continues to focus on ideas that impact the new generation of "digital natives"--Managers who are at home in the digital world and expect to leverage technologies in their business lives. Brief, yet complete, this text provides a basic framework for understanding the relationships among business strategy, information systems, and organizational strategies. Whether you're coming from IS or the business management side, Managing and Using Information Systems, fifth edition, will give you a valuable grasp of how technologies affect business decisions, so you can grab every opportunity for business success.
The information systems strategy triangle -- Strategic use of information resources -- Organizational strategy and information systems -- Information systems and the design of work -- Information system for managing business processes -- Architecture and infrastructure -- The business of IT -- Governance of the information system organization -- Information systems sourcing -- Managing IT projects -- Knowledge management, business intelligence and analytics -- Using information ethically.
Includes index.
Keywords: KNOWLEDGE MANAGEMENT; INFORMATION TECHNOLOGY -- MANAGEMENT; MANAGEMENT INFORMATION SYSTEMS